The prevalence of non-communicable disease among high-risk population in Pattimura University - Bertha Jean Que (BIOEDUPAT: Pattimura Journal of Biology and Learning, 2023)
Increasing the case of Non-Communicable Diseases (NCDs) can cause the biggest problems in the future. Preventive efforts and control of this condition are made through a screening approach for high-risk age groups. This study aimed to determine the prevalence of NCDs among lecturers and staff of high-risk populations at Pattimura University. This study is descriptive quantitative research with a cross-sectional approach conducted using a screening method. A total of 517 were involved in this study which was dominated by female sex (65%), stage 1 hypertension based on systolic blood pressure (36%), stage 2 hypertension based on diastolic blood pressure (30%), normal heart rate (98%), BMI obesity degree 2 (41%), central obesity or abdominal circumference more than normal (52%), normal blood sugar levels (81%), normal uric acid levels (73%), and normal cholesterol levels (58%). It means that the most prevalent NCDs in the population tend to be hypertension and obesity. Good management and education must control the risk factor to prevent morbidity and mortality